PERLINDUNGAN HUKUM BAGI KONSUMEN DALAM TRANSAKSI JUAL BELI ONLINE (E-COMMERCE): ASAS ITIKAD BAIK SEBAGAI PRINSIP KOREKTIF DALAM PERLINDUNGAN KONSUMEN ONLINE - Umul Khair; Yefrianto Yefrianto (Ensiklopedia of Journal, 2026)
Abstract: The rapid development of computer, telecommunication, and information technologies has significantly increased the number of internet-based transactions worldwide. Legal protection for consumers in online buying and selling transactions is therefore essential to support the sustainable growth of the community’s economy. This study examines the responsibility of business actors toward consumers in online sales transactions and the forms of legal protection available to consumers in online sale and purchase agreements. This research employs a normative legal research method by analyzing relevant laws and regulations. The results indicate that, first, business actors in online sales transactions are obligated to provide compensation or indemnification for defective or problematic products. Second, legal protection for online consumers is provided through legal certainty as stipulated in statutory regulations governing electronic transactions, particularly Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 on Information and Electronic Transactions, and Law Number 8 of 1999 on Consumer Protection.  Keywords: Consumer Protection, Agreement, Online Sale and Purchase.